A Systematic Mapping Study on Applications for Multi-core and Many-core Architectures for Protein Structure Prediction - Lopes, Gesiel Rios; Delbem, Alexandre C. B. (Anais da Escola Regional de Computação do Ceará, Maranhão e Piauí (ERCEMAPI); 2019: Anais da VII Escola Regional de Computação do Ceará, Maranhão e Piauí, 2019)
Proteins are the most abundant organic compounds of living matter and perform essential functions to the life's process. Given a proteins amino acid sequence, the Protein Structure Prediction (PSP) problem is to find a three-dimensional structure that has the native energy level. It can help in the design of new drugs and medicine. However, despite advances made in recent years, the development of methodologies capable of achieving a high degree of predictability and accuracy remains a major challenge. This systematic mapping aims to find related studies and research opportunities of how multi-core and many-core architectures have been used to solve the PSP problem. We have defined a systematic mapping process and applied it to complete a systematic mapping study. Thirty-two primary studies were selected for discussions on advances and opportunities for further investigations. The results show that there is an increasing interest to apply solutions based on multi-core and many-core architectures for this computing hard problem.